Petty Corruption Handling That Unconformity The Elements Of Restorative Justice Approach - Azzah, Anisah; Wiwik Afifah; Muh Jufri Ahmad (International Conference of Innovation and Community Engagement, 2024)
This research focuses on handling petty corruption which does not meet the elements of using a restorative justice approach. Petty's various corruption crimes have been detrimental to state finances. The limitation on state losses that can be categorized as petty corruption is below 100 million rupiah, while the costs that will be incurred to complete the formal legal process can reach 100 million rupiah or more. An alternative for handling petty corruption cases is by applying a restorative justice approach model to reduce state losses. The research was carried out using normative research methods with a conceptual approach and a statutory approach. The research results show that the restorative justice approach cannot be used as an alternative to resolve petty corruption because corruption regulations require criminal punishment for perpetrators of corruption even though they have repaid state losses. The restorative justice approach is not used in order to provide a deterrent effect for perpetrators of corruption and prevent the recurrence of criminal acts of corruption as well as a precedent for perpetrators who have the potential to commit subsequent criminal acts of corruption. An alternative punishment that can be used is to increase the fines for corruptors, so that the government can cover state losses that occur while case files are being processed in court.